2010
DOI: 10.1186/1756-9966-29-171
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression and impact of prostate specific membrane antigen and prostate specific antigen in prostatic pathologies

Abstract: BackgroundThe present study was undertaken to relate the co-expression of prostate-associated antigens, PSMA and PSA, with the degree of vascularization in normal and pathologic (hyperplasia and cancer) prostate tissues to elucidate their possible role in tumor progression.MethodsThe study was carried out in 6 normal, 44 benign prostatic hyperplastic and 39 cancerous human prostates. Immunohistochemical analysis were performed using the monoclonal antibody CD34 to determine the angiogenic activity, and the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
(54 reference statements)
3
26
0
Order By: Relevance
“…In our series, the expression of PSMA was significantly greater in higher tumor advancement and grade and was larger than that of PSA in poorly differentiated tumors, which confirms earlier studies [19]. Our finding is consistent with previous reports using immunohistochemistry and multiplex PCR reaction to demonstrate the association between PSMA and tumor progression [37,38]. The mean LI PSMA value in our study was 44.1% and was within the range (30-100%) given by different authors [19,20,36,37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our series, the expression of PSMA was significantly greater in higher tumor advancement and grade and was larger than that of PSA in poorly differentiated tumors, which confirms earlier studies [19]. Our finding is consistent with previous reports using immunohistochemistry and multiplex PCR reaction to demonstrate the association between PSMA and tumor progression [37,38]. The mean LI PSMA value in our study was 44.1% and was within the range (30-100%) given by different authors [19,20,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is consistent with previous reports using immunohistochemistry and multiplex PCR reaction to demonstrate the association between PSMA and tumor progression [37,38]. The mean LI PSMA value in our study was 44.1% and was within the range (30-100%) given by different authors [19,20,36,37]. The difference in the mean values might be caused by non-equal number of cases in the analyzed tumor grade groups (value ranges were similar).…”
Section: Discussionsupporting
confidence: 92%
“…This discordance together with the limited spatial resolution of PET limits the accuracy of PSMA-based tumor characterization and might well have caused false-negative findings by 68 Ga-PSMA PET/CT. Furthermore, primary lesions often coexist with hyperplasia, which is associated with increased PSMA expression (16). The high background signal of the prostate may mask the difference between histopathology-positive and -negative segments, especially in those segments with a GS of 6 or a low STB.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that when the PSMA -/PSA + profile decreased in normal prostates, benign prostatic tissue, and primary prostate cancers, the PSMA + /PSAlevel increased from normal to prostate tumor tissues. Generally, researchers support the idea that the amount of PSMA and/or PSA in healthy men is low in the blood and it increases either with age or because of inflammation of prostate gland (prostatitis) or prostatecancer [16,17,21,22,23] To decrease the side effects of any prostate therapy, it is crucial to develop a good screening pattern for preventing the disease. Finding a tumor at an early stage may be easier to treat before it will cause serious symptoms.…”
Section: Discussionmentioning
confidence: 99%